2014
DOI: 10.1371/journal.pone.0102026
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids Reduce Endocytosis of High-Density Lipoprotein (HDL) in HepG2 Cells

Abstract: High-density lipoprotein (HDL) transports lipids to hepatic cells and the majority of HDL-associated cholesterol is destined for biliary excretion. Cholesterol is excreted into the bile directly or after conversion to bile acids, which are also present in the plasma as they are effectively reabsorbed through the enterohepatic cycle. Here, we provide evidence that bile acids affect HDL endocytosis. Using fluorescent and radiolabeled HDL, we show that HDL endocytosis was reduced in the presence of high concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Our data indicate that there are differences in the effects of HDL on LPS and LTA uptake—namely that HDL may reduce uptake of LPS, but has no effect on LTA uptake. These findings are somewhat paradoxical as both LPS and LTA are known to incorporate into HDL 21 , 22 , and studies have shown that HepG2 cells can internalize HDL particles 35 . Furthermore, since LDLR can bind to apoE 36 , which is found on a subset of HDL particles 37 , it was expected that some uptake of HDL and incorporated bacterial lipids might occur through LDLR.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that there are differences in the effects of HDL on LPS and LTA uptake—namely that HDL may reduce uptake of LPS, but has no effect on LTA uptake. These findings are somewhat paradoxical as both LPS and LTA are known to incorporate into HDL 21 , 22 , and studies have shown that HepG2 cells can internalize HDL particles 35 . Furthermore, since LDLR can bind to apoE 36 , which is found on a subset of HDL particles 37 , it was expected that some uptake of HDL and incorporated bacterial lipids might occur through LDLR.…”
Section: Discussionmentioning
confidence: 99%